Role of Micro ESR in the Evaluation of Neonatal Sepsis - Kafle, Raju; Yadav, Jaydeep; Gupta, Binod Kumar; Gupta, Badri Kumar (Journal of Universal College of Medical Sciences, 2019)
INTRODUCTION: In a developing country like Nepal, where proper medical care and obstetrical facilities are still scarce in the rural areas, neonatal sepsis is a major cause of neonatal morbidity and mortality. With limited resources, early diagnosis and treatment if crucial, may not be achieved. Objective of this study is to evaluate the role of micro ESR in the diagnosis of neonatal sepsis. MATERIAL AND METHODS: A prospective analytical study was done where all neonates with suspected sepsis admitted in NICU were included in the study. Micro-ESR was measured with relevant septic screening investigations. The micro-ESR was compared with age specific cut off value and the results were compared with various clinical presentations, laboratory findings and outcome variables. RESULTS: Out of 250 neonates, micro-ESR was elevated in 12% (29 neonates) of cases. Total proven sepsis is 6%, probable sepsis 60.8% and no sepsis in 33.2%. Correlation of elevated micro ESR was statistically significant with presence of clinical symptoms, clinical and systemic signs. It had significant clinical association with blood culture and CSF findings. The sensitivity, specificity and positive and negative predictive value of micro ESR compared to blood culture was 93.3%, 93.6%, 48.3% and 99.5%. CONCLUSION:- Micro ESR is a simple, relatively cheap and sensitive study in prediction of neonatal sepsis. It can be useful test in settings with limited resources.